The Nominee Agreement in Bali - I Wayan Werasmana Sancaya; Nella Hasibuan Oâ€™Leary (Sociological Jurisprudence Journal, 2019)
The title of this research is â€œThe Nominee Agreement in Baliâ€. It aims discuss the meaning of the nominee agreement and the nominee agreement system in Bali. The study applies normative research approach to discuss about the nominee agreement and its system in Bali. The result is a nominee is a person or firm whose name is used as a guarantee for other properties used to facilitate transactions, while leaving the customer as the actual owner. The nominee agreement itself can be explained as follows. In a nominee agreement, the owner conveys property to a nominee to whom the latter consents to hold and execute transactions on behalf of the owner. The purpose of the agreement is to provide outlines for legal purposes of the ownership of certain property and the role of the nominee. The nominee agreement made by the notary which consists of overpower of the freehold land belonging to Indonesian citizens by foreigners wihout legal power and is null and void when it is promised that foreigners can control the freehold land juridically and have a bad faith when making the nominee agreement.